If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (X + 26) + 70 + 90 = 180 Reorder the terms: (26 + X) + 70 + 90 = 180 Remove parenthesis around (26 + X) 26 + X + 70 + 90 = 180 Reorder the terms: 26 + 70 + 90 + X = 180 Combine like terms: 26 + 70 = 96 96 + 90 + X = 180 Combine like terms: 96 + 90 = 186 186 + X = 180 Solving 186 + X = 180 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-186' to each side of the equation. 186 + -186 + X = 180 + -186 Combine like terms: 186 + -186 = 0 0 + X = 180 + -186 X = 180 + -186 Combine like terms: 180 + -186 = -6 X = -6 Simplifying X = -6
| 5x-12=3(x-4) | | 2+11x=-28+6 | | 2(7+3t)=-1t | | 11=5-2(2y-3) | | 7d+d+4d+5=6d | | m+19=24 | | h^2-8h+12=0 | | 7t-8=2t+32 | | (X+60)+60+65=180 | | 3x+4=2+5x | | -4+7x=-11 | | 4(k+8)=68 | | t^2+6X=-9 | | 11x^2+2x-154=0 | | 7(x-1)=6(x-7) | | 8a^2b+ab^2-2ab= | | 9=6-2(6t-1) | | -2(x-2)=-24 | | p-3=14+7p+4-3p | | (3-u)(5u+9)=0 | | (X+67)+35+90=180 | | Secs-2=0 | | 53=-2-5x | | 9m^2+3=52 | | 3(x+3)=7x-2 | | 3x-5=-7x-33 | | 4(3b-5)=(2b+4) | | (9x+3)+55+50=180 | | k-8/2=8 | | 7(x+6)=6x-1 | | 7n-8(n-3)=18 | | 100t=2.5 |